Pengaruh Debt To Asset Ratio, Return On Asset Earning Per Share Terhadap Harga Saham Pada Perusahaan Farmasi Yang Terdaftar Di Bursa Efek Indonesiaperiode 2015-2019 - Dody Salden Chandra (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2021)
This study aims to determine the effect of Debt to Asset Ratio, Return on Investment, and Earning Per Share on Stock Prices. With a population of pharmaceutical companies listed on the Indonesia Stock Exchange for the 2015-2019 period. This research uses an Associative Quantitative approach. The sample in this study was determined by purposive sampling technique, so that the samples that met the criteria in the sampling for this study were 8 companies. Data collection techniques in this study using documentation techniques, with data analysis techniques using Multiple Linear Regression Analysis. The results of this study concluded that partially there is no effect on Debt to Asset Ratio on Stock Prices, partially negative effect on Return on Investment Stock Prices, Partially there is a positive influence between Earning Per Share on Stock Prices, and simultaneously Debt to Asset Ratio, Return on Investment, and Earning Per Share have a significant effect on share prices in pharmaceutical companies listed on the Indonesia Stock Exchange for the 2015-2019 period.